2020
DOI: 10.3390/pharmaceutics12090842
|View full text |Cite
|
Sign up to set email alerts
|

Click-Free Synthesis of a Multivalent Tricyclic Peptide as a Molecular Transporter

Abstract: The cellular delivery of cell-impermeable and water-insoluble molecules remains an ongoing challenge to overcome. Previously, we reported amphipathic cyclic peptides c[WR]4 and c[WR]5 consisting of alternate arginine and tryptophan residues as nuclear-targeting molecular transporters. These peptides contain an optimal balance of positive charge and hydrophobicity, which is required for interactions with the phospholipid bilayer to facilitate their application as a drug delivery system. To further optimize them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Moreover, these bicyclics also selectively inhibited proliferation of cisplatinresistant ovarian cancer cells, as evidenced by their low μM IC50 values. [62]. This tricyclic enhanced cellular uptake of fluorescently labeled phosphopeptide (F'-GpYEEI), anti-HIV drugs (e.g., lamivudine, emtricitabine, stavudine), and siRNA by cells of the breast cancer cell line MDA-MB-231.…”
Section: Concurrently [W 5 G]-(triazole)-[kr 5 ] and [W 5 E]-(β-ala)-...mentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, these bicyclics also selectively inhibited proliferation of cisplatinresistant ovarian cancer cells, as evidenced by their low μM IC50 values. [62]. This tricyclic enhanced cellular uptake of fluorescently labeled phosphopeptide (F'-GpYEEI), anti-HIV drugs (e.g., lamivudine, emtricitabine, stavudine), and siRNA by cells of the breast cancer cell line MDA-MB-231.…”
Section: Concurrently [W 5 G]-(triazole)-[kr 5 ] and [W 5 E]-(β-ala)-...mentioning
confidence: 98%
“…Reprinted with permission from[60]. Copyright 2018 American Chemical Society.Recently, research groups have synthesized tricyclic peptides, including a trimer of monocyclic peptide [WR] 4 named [WR] 4 -[WR] 4 -[WR]4[62]. This tricyclic enhanced cellular uptake of fluorescently labeled phosphopeptide (F'-GpYEEI), anti-HIV drugs (e.g., lamivudine, emtricitabine, stavudine), and siRNA by cells of the breast cancer cell line MDA-MB-231.…”
mentioning
confidence: 99%
“…Two bicyclic peptides containing tryptophan and arginine residues, namely [W The confocal microscopy exhibited that the peptides were localized in the nucleus and cytosol [219]. Recently, we designed a tricyclic peptide [WR] 4 -[WR] 4 -WR] 4 containing alternate tryptophan and arginine in each ring that improved the cellular uptake of F'-GpYEEI and fluorescently labeled anti-HIV drugs, lamivudine (3TC), emtricitabine (FTC), and siRNA in the breast cancer cell line MDA-MB-231 [221]. A combination of tryptophan and arginine residues in the design provided a diverse class of cyclic CPPs with differential cellular delivery properties.…”
Section: Peptide-based Therapies 71 Monocyclic Bicyclic and Tricyclic Cell-penetrating Peptides As Molecular Transportersmentioning
confidence: 99%
“…A recent study showed enhanced inhibition of proliferation of cancer cell lines by nanoparticle-encapsulated Lamivudine compared with the free Lamivudine ( 48 ). Other works had assayed some cysteine and arginine rich peptides ( 49 ) and multivalent tricyclic peptides ( 50 ) as vehicles to deliver Lamivudine into the target cells. In the first case, a number of cysteine and arginine containing linear and cyclic peptides were challenged to see whether these peptides could improve the intracellular transportation of two cargoes, a fluorescently-labeled and cell-impermeable phosphopeptide (F´-GpYEEI) and fluorescently-labeled Lamivudine (F-3TC).…”
Section: Repurposing Nucleoside/nucleotide Antivirals In Cancermentioning
confidence: 99%
“…In the second case, a trycyclic peptide was constructed with an optimal balance of positive charge and hydrophobicity to improve its interactions with the cell membranes and promote transport of the cargo; in this case fluorescently labeled anti-HIV drugs such as F´-Lamivudine (F´-3TC), F´-Emtricitabine (F´-TC), and F´-Stavudine (F´-d4T). In all cases, the trycyclic peptide used as molecular transporter enhanced the cellular uptakes of these fluorescently labeled pro-drugs ( 50 ). In summary, new delivery strategies are being optimized to improve the entrance of Lamivudine and other ANNAs into target cells ( Figure 1B ), which could support the repurposing of Lamivudine and other ANNAs to work as direct anti-cancer therapies in vitro and in vivo .…”
Section: Repurposing Nucleoside/nucleotide Antivirals In Cancermentioning
confidence: 99%